THE EFFECT of PINEALOCTOMY on the DEVELOPING SUPERIOR Cervical GANGLION of the RAT - Ali, Hadi Jawad; Al-khafaji, Fadhil A.; Hamash., Mahmood H. (AL-Kindy College Medical Journal, 2011)
Back ground: In the present study Pinealoctomy was used to study the sympathetic innervations of the pineal gland by the superior cervical ganglion (SCG) of the albino rat. Objective: Following Pinealoctomy, it is expected to observe the Chromatolysis reaction in some neurons of the SCG if they were to innervate the pineal gland (i.e. retrograde Chromatolysis changes). Methods: Fifty albino rats were used in this study, Pinealoctomy was done, then after a different time interval ganglionectomy was done, in order to study the Chromatolysis in their cell body. Result: The present study has demonstrated that the most obvious Chromatolysis reaction in the neurons which innervate the pineal gland appeared one day following Pinealoctomy in the young and adult rats. In the SCG of animal, one week following Pinealoctomy, the number of the Chromatolysis neurons was much less than these seen in the previously mentioned one day animals. In (2 – 6) weeks following Pinealoctomy, the number of the Chromatolysis neurons kept a constant decline. Conclusion: The work presented in this study showed that the method of tracing the innervations of the pineal gland by removing the target tissue (the pineal gland in this study) appeared to be justified and conclusive. It has also shown that younger animals, subjected to Pinealoctomy, would react more vigorously with respect to Chromatolysis than adult animals. The present study has also demonstrate that the distribution of these Chromatolysis neurons and for all age groups all over the ganglion being inspected. However they were more abundant in the rostral 2/3 of these ganglions.